Pengaruh Komitmen Kerja dan Kepribadian terhadap Motivasi Kerja Karyawan pada PT. Pegadaian (Persero) Kantor Wilayah VI Makassar - Sitti Masyita; Buranda, Thania Engel (Insan Cita Bongaya Research Journal, 2023)
This study aims to examine and analyze the effect of work commitment and personality on the work motivation of employees of PT. Does personality affect employee motivation. This research was conducted at the company PT. Pegadaian ( Persero ) Regional Office VI Makassar. The sample technique used to determine the sample size, this research technique is non-probability sampling with a sample size of 55 people. The results of the questionnaire have been tested for validity and reliability, also tested for classical assumptions in the form of normality assumptions, multicollinearity assumptions and heteroscedasticity. Methods of data analysis using multiple regression techniques. The results of testing the hypothesis prove that there is no effect of work commitment on work motivation. While personality influences the work motivation of employees of PT. Pegadaian ( Persero) Regional VI Makassar Office